Genomic and Functional Analysis of Emerging Virulent and Multidrug-Resistant Escherichia coli Lineage Sequence Type 648 - Schaufler, Katharina; Semmler, Torsten; Wieler, Lothar H; Trott, Darren J; Pitout, Johann; Peirano, Gisele; Bonnedahl, Jonas; Dolejska, Monika; Literak, Ivan; Fuchs, Stephan; Ahmed, Niyaz; Grobbel, Mirjam; et al. (Antimicrobial agents and chemotherapy, 2019)
The pathogenic extended-spectrum-beta-lactamase (ESBL)-producing Escherichia coli lineage ST648 is increasingly reported from multiple origins. Our study of a large and global ST648 collection from various hosts (87 whole-genome sequences) combining core and accessory genomics with functional analyses and in vivo experiments suggests that ST648 is a nascent and generalist lineage, lacking clear phylogeographic and host association signals. By including large numbers of ST131 (n = 107) and ST10 (n = 96) strains for comparative genomics and phenotypic analysis, we demonstrate that the combination of multidrug resistance and high-level virulence are the hallmarks of ST648, similar to international high-risk clonal lineage ST131. Specifically, our in silico, in vitro, and in vivo results demonstrate that ST648 is well equipped with biofilm-associated features, while ST131 shows sophisticated signatures indicative of adaption to urinary tract infection, potentially conveying individual ecological niche adaptation. In addition, we used a recently developed NFDS (negative frequency-dependent selection) population model suggesting that ST648 will increase significantly in frequency as a cause of bacteremia within the next few years. Also, ESBL plasmids impacting biofilm formation aided in shaping and maintaining ST648 strains to successfully emerge worldwide across different ecologies. Our study contributes to understanding what factors drive the evolution and spread of emerging international high-risk clonal lineages.
Keywords: kur domácí; Plasmids; Virulence; beta-laktamasy; infekce močového ústrojí; Chickens; plazmidy; Escherichia coli; Humans; virulence; Multilocus Sequence Typing; biofilmy; zvířata; infekce vyvolané Escherichia coli; antibakteriální látky; genomika; Biofilms; Whole Genome Sequencing; Genomics; Virulence Factors; Escherichia coli Infections; multilokusová sekvenční typizace; bakteriemie; Urinary Tract Infections; beta-Lactamases; Bacteremia; sekvenování celého genomu; mnohočetná bakteriální léková rezistence; Animals; Drug Resistance, Multiple, Bacterial; lidé; Anti-Bacterial Agents; faktory virulence